Effectiveness of Online Stress Relief Programs of Public Health Volunteers, Nong Ma Mong Hospital, Nong Ma Mong District, Chainat Province - ยอดอ่อน ธันย์สิตา (Journal of Health Science of Thailand, 2022)
In the situation of the epidemic of COVID-19, public health volunteers have to perform their duties as a front line. Being proactive in the community have resulted in stress and fear of contracting the disease. Furthermore, the social distancing policy has limited the opportunity for the volunteers to communicate face-by-face or perform group activities to relieve the stress. The objective of this study was to assess the effectiveness of an online stress relief program forpublic health volunteers. It was a quasi-experimental study measuring the outcomes before and after the experiment. The sample consisted of 27 public health volunteers who received an online stress relief program consisting of meditation therapy, thought-stopping practice, together with meditation and basic mindfulness sleep with music for a total of 4 weeks. Data were collected before and after receiving the program. A 20-item stress test was used to measure the outcomes. The data were analyzed using descriptive statistics, paired t-test and Wilcoxon Matched-pairs signed-ranks test. It was foun that before joining the program the volunteers had an average mean stress score of 2.29 (SD=0.47). After implementing the program, the average mean score was found to be 2.00 (SD=0.62), which indicated that the program had statistically significantly reduced the stress (p<0.05). The sum of the mean scores before the program was 38.03 (SD=9.05) which was at a moderate stress level; and after joining the program, the total mean scores was slightly reduced to 34.33 (SD=9.59), also at a moderate level. The decline of overall mean stress scores after the program was statistically significant (p<0.05).